Epworth League California Convention at Monte Toyon - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of attendees of the Epworth League California Convention at Monte Toyon. Several groups of attendees are holding signs or banners that read: "Santa Cruz First M.E.," "Tracy," "Watsonville," "Theta Pi," "Hollister," "San Leandro," "Manteca," "Long Beach," "Burlingame," "San Mateo," "Kappa Phi Sigma."